Software for a smart thermodynamics-based fast battery analyser/charger - Rao, Abhinav (2019)
Batteries have begun to play a very important role in our lives. Their application ranges from small capacity, single use cells to large capacity packs (in-development) capable of independently powering energy requirements as big as those of trucks running over hundreds of kilometres like the one by Tesla [1]. Batteries are broadly classified into rechargeable and non-rechargeable. Rechargeable batteries are used in many modern electronic devices like laptops, mobile phones, and even cars. The life of a battery directly affects the availability of a device to the consumer. This also influences the buying decision of a potential customer. Further, batteries are being considered as the future source of power. They can be used to store renewable energy when it is available and provide power when required. This is being done at very large scales around the world [2]. Hence, a lot of progress has been made in battery research, and further research is being done vigorously for improving batteries. This project is an effort in that direction. This project used lithium-ion (Li-ion) batteries to conduct experiments. The aim was to implement software applications that run tests on these batteries, collect and analyse the data gathered after the tests. Two software applications were used for running tests on the Battery Analyser 3000 (BA3000) machine and using Espec chamber for temperature control (explained in section 2.2). One more software application was developed as a tool exclusively for data analysis. These applications were designed as per requirements from stakeholders at KVI Battery Technologies Ltd., an NTU start-up enterprise. Front-end and back-end components of the applications were developed using C# programming language. A locally set up MySQL database component was used for storing testing parameters. Test results and logs were collected and stored as CSV files for flexibility of use and further analysis. The development was performed on Microsoft 3 Visual Studio 2015 running on a MS Windows 7 machine. The data analysis tool used excel worksheets as input data for analysis and provided output as XML files. These applications were able to fulfil the requirements from KVI. The data collected from testing cells by using these applications will be analysed further by KVI. It will be used for further improvements in cell technology. The collected data is represented in section 5 of the report.